Criteria for designing Smart Micro-learning Environments to develop Cognitive Mastery in the Biology Course for Secondary School Students in The Kingdom of Saudi Arabia - Al-Nasheri, Ali Ahmed; Zeidan, Ashraf Ahmed; Al-Shehri, Bassim Rafi (Journal of Curriculum and Teaching Methodology, 2025)
The current research aimed to determine the criteria for designing smart microlearning environments to develop cognitive mastery among secondary school students in the Kingdom of Saudi Arabia in the biology Course. A descriptive analytical approach was used in preparing a list of educational and technical criteria associated with the design of the smart microlearning environment based on literature about smart microlearning environments , the general characteristics of the biology Course for the secondary stage And the principles of cognitive mastery. The research tool was a questionnaire that included the proposed standards. Researchers validated and presented the questionnaire to a sample of experts specialized in educational technologies. Cooper’s equation was used to calculate the percentage of agreement on the list of criteria and their indicators.. The results indicated that the list of criteria for designing smart microlearning environments included two main fields: the field of educational criteria, which included (4) main criteria with a total of (49) performance indicators, the second field included technical criteria, having (3) main criteria with a total of (30) performance indicators. The percentage of agreement on all educational standards and their indicators was (96%), and the percentage of agreement of the arbitrators on the field of technical and technical craiteria was (97%). Thus, the percentage of agreement on the list of criteria according to the Cooper equation reached (96.5%), which is an appropriate value for the adoption of the criteria items in their final form. Therefore, the study recommends taking advantage of the list of criteria and relying on them when designing smart microlearning environments to develop cognitive mastery in the biology course for secondary school students.